The newtonian theory of time and its understanding in Kant - Gloy, Karen; Rendón, Carlos Emel (Estudios de Filosofía, 1993)
The problem is posed in a present day perspective, in view of criticism coming from Physics (Theory of Relativity), Philosophy (the Phenomenology of the subjective and perceptional strata of time) and the Science of Culture (Ethnology and Philosophy of Religion). The modification of the Newtonian concept of time introduced by Kant is then explained and a study is finally undertaken of the advantages and disadvantages Kant' s pure positional time would have in reference to the modal-temporal structure, should there be an interest in passing from what is subjective to what is objective in time.